Contemporary management strategies and outcomes in patients with Non ST elevation myocardial infarction. (14th October 2021) - Orso, F; Casolo, G; Szasz, C; Forni, S; D'Arienzo, S; Gemmi, F
Abstract: Background: Non-ST-elevation myocardial infarction (NSTEMI) is a condition that is associated with a high morbidity and mortality burden. The aim of the present study is to analyze clinical characteristics and outcomes of a large contemporary population of NSTEMI patients according to treatment strategy in a large administrative database. Methods: This retrospective observational study included patients living in the region of Tuscany, aged 18 years or older who were discharged from a regional hospital with a diagnosis of NSTEMI (principal diagnosis ICD-9-CM codes 410.7 or 411.1 in HDA) between January 2016 and December 2018. According to management strategy patients were classified in two main groups: a conservative strategy (CON) group and an invasive strategy (INV) group which was further categorized in three subgroups: a PCI group, a CABG group and a group were patients were invasively managed but medically treated. Results: The study population was composed by 15.208 patients. Mean age was 76±9 years, with 50% aged 75+ years, females were 38.5%. Management strategies groups composition was: CON strategy 24.9% and among INV strategy (75.1%) 67.3% were treated by PCI, 8.8% by CABG and 24% were invasively managed but medically treated. Compared to INV managed patients, patients in the CON group were older (mean age 85 vs 72 years, p<0.0001), more frequently female (54% vs 33%, p<0.0001), had a higher cardiovascular and non-cardiovascular comorbidity burden (eg. hypertension, diabetes, heart failure, atrial fibrillation, renal insufficiency, cancer, dementia and COPD, all <0.0001). In-hospital, 30-days and 1-year all-cause mortality rates (Figure) were 3%, 4.9% and 15.3% resulting significantly higher in the CON management strategy group compared to the INV strategy group: 8.9% vs 1.1; 14.0 vs 1.9%; all p<0.0001. Analyzing all-cause mortality rates among the three INV subgroups we found no differences both in-hospital and at 30 days, while at 1-year we found, all-cause mortality there was a significant difference among the three groups with a slightly higher mortality rate in the INV medically treated group compared to the PCI and the CABG subgroups: 8.9% vs 7.2% vs 7.5% respectively, p=0.011. Conclusions: Real-world evidence show that patients with NSTEMI have significantly different characteristics and outcomes according to management strategy. Patients managed non-invasively have more complex features and worse outcomes both in-hospital and post-discharge. Patients which were managed invasively but medically treated represent an interesting subgroup which may deserve further evaluation. FUNDunding Acknowledgement: Type of funding sources: None.